(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
These difficulties, being features of the disorder, can hinder treatment, by definition, an interpersonal process. The aim of the present study is to argue how, paradoxically, the exploration of difficulties in the relationship can help make treatment more efficient. The method was a case study, using participant observation. Tools from different behavioral treatments, ACT, DBT and FAP made a flexible way of dealing with the challenges of the relationship with the borderline client possible. Polk’s matrix helped monitor the experience of the therapist. The analysis of alliance ruptures and the therapist’s emotional responses toward treatment helped the client learn about herself and her relational world. Together, these tools made it possible to work directly with what was occurring in the therapeutic relationship and permitted to harness the difficulties encountered for the benefit of the process. The study suggests that integrating the contributions of diverse theoretical currents in the contemporary behavior therapy movement can make treatment of difficult cases more efficient, aiding to overcome paradigmatic rigidity